Incremental Security Enforcement for Cyber-Physical Systems - Panda, Abhinandan; Baird, Alex; Pinisetty, Srinivas; Roop, Partha (IEEE access, 2023)
Cyber-Physical attacks (CP-attacks) are launched either from the cyber-space or from the physical-space to take control of a Cyber-Physical System (CPS). Unlike conventional cyber-attacks, which are prevented through new security patches as new attacks emerge, there are no known mechanisms for incrementally patching CPS in the event of new attacks. To this end, we develop a novel approach based on recent advances in mitigating CP-attacks using run-time enforcement (RE). RE-methods have been developed for CPS, such as industrial processes and pacemakers. However, the proposed solutions are not developed considering the need for future patching as new attacks emerge. To this end, we develop the first compositional RE framework, which is specifically developed to be able to add new security patches as new security policies are added. We illustrate our approach using the case study of a drone swarm. The experimental results show that the proposed compositional/incremental approach does not suffer from the state space explosion, unlike the monolithic composition. We demonstrate a linear relationship between compile time, compile size, and execution time as the number of policies increases in the proposed compositional scheme.